It's about Time? Testing the Dawson Ceramic Seriation Using Luminescence Dating, Southern Nasca Region, Peru. Issue 4 (December 2014) - Vaughn, Kevin J.; Eerkens, Jelmer W.; Lipo, Carl; Sakai, Sachiko; Schreiber, Katharina
Abstract : The Dawson seriation of Nasca ceramics has long been assumed to be an accurate marker of temporal changes in the prehispanic south coast of Peru. We test this assumption by directly dating a sample of sherds using Optically Stimulated Luminescence (OSL). Our results suggest that while some phases of the seriation are valid chronological markers, others appear to be the result of factors other than time. We discuss the implications of these results and call for additional studies of ceramics using luminescence dating